2002
DOI: 10.1097/00006534-200201000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Contour Abnormalities of the Abdomen after Breast Reconstruction with Abdominal Flaps

Abstract: The purpose of the present study was to determine whether contour abnormalities of the abdomen after breast reconstruction with abdominal flaps are related to the harvest of the rectus abdominis muscle. Abdominal contour was analyzed in 155 women who had breast reconstruction with abdominal flaps; 108 women had free transverse rectus abdominis muscle (TRAM) flaps, 37 had pedicled TRAM flaps, and 10 had deep inferior epigastric perforator (DIEP) flaps. The reconstruction was unilateral in 110 women and bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(102 citation statements)
references
References 26 publications
3
95
0
4
Order By: Relevance
“…This has been previously demonstrated. 33,34 There does not appear to be a difference when comparing the MS-3 group to the MS-2 group. The supportive aspect of the anterior abdominal wall appears to be related primarily to the integrity of the anterior rectus sheath.…”
Section: Discussionmentioning
confidence: 93%
“…This has been previously demonstrated. 33,34 There does not appear to be a difference when comparing the MS-3 group to the MS-2 group. The supportive aspect of the anterior abdominal wall appears to be related primarily to the integrity of the anterior rectus sheath.…”
Section: Discussionmentioning
confidence: 93%
“…28,37,38 Studies have shown that use of this flap results in less donor-site morbidity of the abdominal wall than free or pedicled TRAM flaps. 36, 39 Ng et al observed that microsurgical techniques alone appear to show better flap perfusion and less frequent herniation and bulging in patients in whom bipedicled TRAM flaps were used than in patients who underwent flap transfer using conventional bipedicled or augmented techniques. 40 The internal mammary and axillary vessels were used simultaneously as recipient vessels for bipedicled free TRAM and bipedicled DIEP flaps.…”
Section: Augmented Trammentioning
confidence: 99%
“…This tissue is supplied by both superficial and deep arterial networks, which can each be used in the supply of this tissue when raised as a flap for use in free tissue transfer. There has been a shift over time to reducing the donor site morbidity in the harvest of this tissue, with sequential sparing of the rectus abdominis muscle from the transverse rectus abdominis musculocutaneous (TRAM) flap, 1,2 to the muscle-sparing TRAM flap, 3,4 and sparing of damage to the nerves innervating the remaining muscle with the use of the deep inferior epigastric artery (DIEA) perforator (DIEP) flap. [5][6][7][8] The ultimate donor-site sparing procedure is the superficial inferior epigastric artery (SIEA) flap, as it does not require any incision of the anterior rectus sheath.…”
mentioning
confidence: 99%